1986
DOI: 10.1128/mcb.6.8.2984
|View full text |Cite
|
Sign up to set email alerts
|

Beta-adrenergic stimulation of c-fos gene expression in the mouse submandibular gland.

Abstract: Isoproterenol (IPR), a 0-adrenergic agonist, induces division of acinar cells in the parotid and submandibular glands of adult rodents and produces hyperplastic and hypertrophic enlargements of these organs. We analyzed the effects of IPR on thymidine incorporation, c-fos mRNA levels, and the immunocytochemical localization of c-fos protein in the submandibular glands of adult and of 5-and 14-day-old mice. In the glands of untreated mice c-fos transcripts were not detectable. In all experimental groups, admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0
2

Year Published

1987
1987
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 33 publications
0
21
0
2
Order By: Relevance
“…Chronic lpr injections induce adaptive growth of both parotid and submandibular glands. This growth is the result of both cell enlargement and a moderate proliferative response of terminally differentiated acinar cells (Brown-Grant, 1961; Schneyer, 1962;Barka et al, 1986). Characteristically, this increase in the size of salivary glands is associated with qualitative and quantitative changes in salivary-specific gene expression, including up-regulation of the major secretory proteins, proline-rich proteins (PRPs), and down-regulation of amylase and parotid secretory protein (PSP) (Poulsen et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic lpr injections induce adaptive growth of both parotid and submandibular glands. This growth is the result of both cell enlargement and a moderate proliferative response of terminally differentiated acinar cells (Brown-Grant, 1961; Schneyer, 1962;Barka et al, 1986). Characteristically, this increase in the size of salivary glands is associated with qualitative and quantitative changes in salivary-specific gene expression, including up-regulation of the major secretory proteins, proline-rich proteins (PRPs), and down-regulation of amylase and parotid secretory protein (PSP) (Poulsen et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Characteristically, this increase in the size of salivary glands is associated with qualitative and quantitative changes in salivary-specific gene expression, including up-regulation of the major secretory proteins, proline-rich proteins (PRPs), and down-regulation of amylase and parotid secretory protein (PSP) (Poulsen et al, 1986). In addition to PRP genes, two immediate-early transcription factors, Fos and Jun, are induced by Ipr-injection (Barka et al, 1986;Kousvelari et al, 1988;Yeh et al, 1992 This review will focus mainly on the regulation of salivary-specific genes such as PRP, amylase, and parotid secretory protein (PSP) expression. We will present information on the identification and characterization of ciselement(s) in the distal enhancer region, which mediates the salivary cAMP-inducibility on one of the major salivary PRP genes, R15.…”
Section: Introductionmentioning
confidence: 99%
“…In the mouse submandibular gland, stimulation of the ␤ -adrenergic receptor by isoproterenol causes a rapid, transient induction of c-Fos expression in both acinar and duct cells, although the biological significance of this phenomenon has not been clarified (Barka et al 1986). In this study, by use of immunochemical and immunohistochemical methods, we demonstrate that many AP-1 family members, primarily JunD, are expressed exclusively in the duct system of mouse submandibular gland, and that JunD expression and localization are regulated in association with the androgen-dependent duct cell differentiation.…”
mentioning
confidence: 99%
“…The effects of catecholamine on the expression of the c-fos gene have not been studied in detail. However, Barka et al (2) reported that the administration of the 3-adrenergic agonist, isoproterenol, induces transient expression of c-fos in the submandibular gland of young mice. Barka's report indicates that binding of epinephrine to adrenergic receptors may be a general mechanism to induce c-fos gene expression.…”
mentioning
confidence: 99%